2022
DOI: 10.3390/nu14142999
|View full text |Cite
|
Sign up to set email alerts
|

What Intervention Elements Drive Weight Loss in Blended-Care Behavior Change Interventions? A Real-World Data Analysis with 25,706 Patients

Abstract: Background: Blended-care behavior change interventions (BBCI) are a combination of digital care and coaching by health care professionals (HCP), which are proven effective for weight loss. However, it remains unclear what specific elements of BBCI drive weight loss. Objectives: This study aims to identify the distinct impact of HCP-elements (coaching) and digital elements (self-monitoring, self-management, and education) for weight loss in BBCI. Methods: Long-term data from 25,706 patients treated at a digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(73 reference statements)
2
8
0
Order By: Relevance
“…Data from the digital stream of the NHS Diabetes Prevention Program revealed a mean weight reduction of 3.1 kg 38 . Roczen is also comparable to other digitally delivered lifestyle interventions, where care is delivered by dietitians or health coaches via digital applications rather than clinicians 39,40 . Our retention rates was comparable to those in other Tier 3 specialist obesity program, with drop out ranging from 10% to 78% at the end of follow‐up 41 .…”
Section: Discussionsupporting
confidence: 55%
“…Data from the digital stream of the NHS Diabetes Prevention Program revealed a mean weight reduction of 3.1 kg 38 . Roczen is also comparable to other digitally delivered lifestyle interventions, where care is delivered by dietitians or health coaches via digital applications rather than clinicians 39,40 . Our retention rates was comparable to those in other Tier 3 specialist obesity program, with drop out ranging from 10% to 78% at the end of follow‐up 41 .…”
Section: Discussionsupporting
confidence: 55%
“…In fact, app users have declared that having professional support for using the apps may be interesting [39]. It has been demonstrated that a combination of care with digital apps-based tools and support by health professionals is effective for healthy weight achievement [72]. The factors included in these interventions, which conditioned the best results in weight management, were as follows: self-management, particularly in the first phases of the interventions; early education in nutrition and diet; and totally online support messages from health professionals [72].…”
Section: Discussionmentioning
confidence: 99%
“…127,128 In addition, several effective behaviour change techniques implicate increasing cognitive awareness and self-efficacy in weight-loss interventions. Self-monitoring of weight or food intake is firmly associated with sustained weight-loss effects and should therefore be strongly encouraged, 129,130 particularly in a weight-loss maintenance phase, at weekly intervals. 111 who participated in a lifestyle intervention program rated a high level of professional supervision as the primary driver of weight loss.…”
Section: Strategies For Successful Communicationmentioning
confidence: 99%
“…In addition, several effective behaviour change techniques implicate increasing cognitive awareness and self‐efficacy in weight‐loss interventions. Self‐monitoring of weight or food intake is firmly associated with sustained weight‐loss effects and should therefore be strongly encouraged, 129,130 particularly in a weight‐loss maintenance phase, at weekly intervals 111 . Other important drivers of behavioural change that should be supported or implemented by HCPs are action planning, providing clear instructions and showing interventions when possible 131 …”
Section: Practical Strategies For Weight Management In Type 2 Diabetesmentioning
confidence: 99%